Local heating of radiation belt electrons to ultra-relativistic energies - Hayley J. Allison (Nature Portfolio, 2020)
Electrons in the Van Allen radiation belts can have energies in excess of 7 MeV, however, the energization mechanism is debated. Here, the authors show phase space density peaks in magnetic coordinate space as a way of analyzing satellite observations which demonstrates that local acceleration is capable of heating electrons up to 7 MeV.